Sobre certos tipos de polinômios de permutação - Pinheiro, Gabriel de Freitas (2022)
In this work, some results regarding permutation polynomials over finite fields will be explored. Initially we will introduce some preliminary concepts about finite fields to later present some criteria to determine when a polynomial over a certain finite field is a permutation one and, finally, we will show some special classes of these polynomials.